Theoretical Study on Destruction Mechanism and Kinetics of Degradation of Toluene by Ozone - Wen, Zhengcheng; Wang, Zhihua; Xu, Jiangrong; Zhou, Junhu; Cen, Kefa (Asian Journal of Chemistry, 2012)
In order to improve the technology of emission of volatile organic compounds removal by ozone, the destruction mechanism and kinetics of degradation of toluene by O3 was investigated employing quantum chemical calculations. Theoretical results showed that, toluene was gradually degraded by O3 via three times cleavages of C=C bonds. All the microcosmic reaction processes were analyzed and depicted in detail based on geometry optimizations made by the UB3LYP/6- 31G(d) method. Furthermore, the kinetic parameters were also calculated by the transition state theory. The activation energy obtained by the QCISD(t)/6-311g(d,p)//UB3LYP/6-31G(d) method was 48.53 kJ/mol, which was in rough agreement with the experimental result (55.81 kJ/mol). The rate constant obtained from the transition state theory was also in good agreement with the experimental result. This indicate that the destruction mechanism and kinetics of degradation of toluene by O3 investigated employing quantum chemical calculations in this paper was fair and reliable.